Transcarotid transcatheter aortic valve replacement combined with percutaneous coronary intervention for severe aortic stenosis with coronary artery disease in a tortuous aortic arch: a Case Report - Wenwen Chen; Yue Bao; Hui Guo (Frontiers in Cardiovascular Medicine)
Transcatheter Aortic Valve Replacement (TAVR) is currently the preferred treatment option not only for high-surgical-risk patients with severe aortic stenosis (AS) but also increasingly for those with intermediate and low surgical risk. Coronary artery disease (CAD) is one of the most common complications in severe AS patients, making percutaneous coronary intervention (PCI) a frequent clinical requirement in cases of severe AS complicated by CAD. The coexistence of Aortic Tortuosity and aortic stenosis is extremely rare.We report a case of an elderly male with severe aortic stenosis combined with coronary artery disease, who underwent successful transcarotid TAVR and PCI due to a Z-shaped fold tortuosity in the aortic arch, making femoral access challenging. The patient was able to ambulate the following day and was discharged on the fifth postoperative day with stable follow-up. As of this writing, no related reports of combined transcarotid TAVR and PCI have been published.